1985
DOI: 10.1002/ar.1092120202
|View full text |Cite
|
Sign up to set email alerts
|

An immunofluorescent analysis of lectin binding to normal and regenerating skeletal muscle of rat

Abstract: Ten different fluorescein-conjugated lectins of various known sugar specificities were used to study cell surface glycoconjugates of normal and regenerating rat skeletal muscle. In normal muscle, Canavalia ensiformis agglutinin, Triticum vulgaris agglutinin (wheat germ agglutinin, WGA), Ricinus communis agglutinin-I, and Maclura pomifera agglutinin bound strongly to the endomysial region of the myofibers. No binding was observed in the cytoplasm of the myofibers. Other lectins (Dolichos biflorus agglutinin, Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Compared to the desmin staining that was lost during early stages of necrosis, lectin binding to the periphery of the muscle fibers was preserved (Helliwell,1988). Gulati and Zalewski (1985) also showed that of four lectins studied only WGA had intense binding in the myogenic zone of regenerating muscle after autotransplantation.…”
Section: Discussionmentioning
confidence: 92%
“…Compared to the desmin staining that was lost during early stages of necrosis, lectin binding to the periphery of the muscle fibers was preserved (Helliwell,1988). Gulati and Zalewski (1985) also showed that of four lectins studied only WGA had intense binding in the myogenic zone of regenerating muscle after autotransplantation.…”
Section: Discussionmentioning
confidence: 92%
“…Such discrepancies, previously emphasized by several authors (Holthofer 1983;Nemanic et af. 1983;Schulte & Spicer 1983;Gulati & Zalewski 1985;Meiniel et a f . 1988;Truong et af.…”
Section: Discussionmentioning
confidence: 99%
“…Although some immunocytochemical investigations on the BL of degenerating and regenerating muscle fibers have been performed (Gulati et al, 1983;Gulati, 1985;Gulati and Zalewski, 1985), further analysis of the properties of muscle fiber BL during degeneration and regeneration has been hampered by the lack of suitable preparative methods. In the current study we describe a method for the generation of acellular muscle samples which exhibit numerous empty tubes of BL which are available for analysis by light microscopy, TEM or SEM.…”
Section: Discussionmentioning
confidence: 99%